Strategic application of nano sulphur and nano calcium for groundnut growth and yield response: A multivariate approach - Kabilan, M; Sakthivel, N; Rajeswari, R; Ramah, K; Rajkishore, S K; Surendrakumar, A; Srimathi, K; Vasumathi, V (Plant Science Today, 2025)
Groundnut (Arachis hypogaea L.) is a significant oilseed crop widely cultivated for its high oil content and nutritional value. To meet the increasing demand for better oil yield and quality, improving productivity through effective nutrient management is crucial. Hence, the field study was conducted at Tamil Nadu Agricultural University to evaluate the effects of foliar applications of nano sulphur and nano-calcium on the growth and yield of groundnut. The experiment involved fifteen treatments with different concentrations and application timings of nano sulphur and nano calcium sprays, evaluated using a Randomised Block Design (RBD). The findings showed that the combined application of nano sulphur at 200 ppm at 30 and 45 Days After Sowing (DAS) (T6) significantly boosted dry matter production, SPAD readings and pod development. T6 also achieved the highest pod yield (2468 kg ha-1), seed yield (1701 kg ha-1), oil yield (820.7 kg ha-1) and oil content (48.27 %), performing comparably to T5 (nano sulphur 100 ppm at 30 & 45 DAS) and T13 (recommended NPK + gypsum). The untreated control (T15) recorded the lowest yields. Correlation and regression analyses demonstrated a strong positive correlation between the total number of pegs and all major yield attributes. The study concludes that nano sulphur at 200 ppm can significantly enhance productivity and oil quality in groundnuts, providing a sustainable alternative to traditional fertilization methods.